2012
DOI: 10.1177/1352458512437418
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and progressive resistance training: a systematic review

Abstract: Recently progressive resistance training (PRT) has been recognised as an effective tool in the rehabilitation of persons with multiple sclerosis (MS). The objective of this study was to systematically review the literature of PRT studies for persons with MS. A comprehensive literature search (PubMed, SveMed+, Embase, Cochrane, PEDro, SPORTDiscus and Bibliotek.dk) was conducted. Identified papers were rated according to the PEDro-scale. Sixteen studies were included and scored between 3 and 8 of 11 total points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
145
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(167 citation statements)
references
References 63 publications
7
145
0
11
Order By: Relevance
“…Despite different subject populations and protocols, studies have consistently reported improvements in muscle strength after training. A review of PRT [Kjolhede et al 2012] examined results from six RCTs of PRT and six noncontrolled trials. The RCTs included subjects with expanded disability status scale (EDSS) scores ranging from 1.0 to 6.5, and duration and intensities of training ranging from 2 to 5 sessions/week over 3-20 weeks.…”
Section: Muscle Strength/mobility/spasticitymentioning
confidence: 99%
“…Despite different subject populations and protocols, studies have consistently reported improvements in muscle strength after training. A review of PRT [Kjolhede et al 2012] examined results from six RCTs of PRT and six noncontrolled trials. The RCTs included subjects with expanded disability status scale (EDSS) scores ranging from 1.0 to 6.5, and duration and intensities of training ranging from 2 to 5 sessions/week over 3-20 weeks.…”
Section: Muscle Strength/mobility/spasticitymentioning
confidence: 99%
“…1 As MSrelated disability progresses to the point where assistance is needed to walk, virtually all people with MS experience weakness. 1 Muscle weakness tends to be more pronounced in the lower than the upper extremities, 2 and it also affects the trunk. 3 Strength training for people with MS can improve strength and has been shown to have an effect on mobility, quality of life, and participation.…”
mentioning
confidence: 99%
“…3 Strength training for people with MS can improve strength and has been shown to have an effect on mobility, quality of life, and participation. 2,4,5 Although there are a variety of measures with favorable psychometric properties available to clinicians to assess changes in mobility and participation after strength training, such as the Timed 25-Foot Walk test, the 2-and 6-Minute Walk Tests, and the Multiple Sclerosis Walking Scale, 6,7 it can be challenging to quantify changes in strength accurately and reliably in a clinical setting.…”
mentioning
confidence: 99%
“…fatigue perception among MS patients [9,10], and resistance training in particular is very useful for this aim [11]. The effects of on MS patients have been studied [12] and incremental improvements in body balance, joint mobility and upper body muscle strength have been observed.…”
Section: Journal Of Neurology and Neurophysiologymentioning
confidence: 99%